Factores asociados en el proceso de producción y comercialización de la Bananera Tres Hermanos del cantón La Maná, provincia de Cotopaxi, año 2021. - Bastidas Quintana, Kerly Melissa (2022)
The current panorama of small banana producers at a national and global level is complex because globalization suggests using new techniques and technologies, developing new knowledge and skills, in order to have greater productivity. The objective of this research is to know the associated factors in the production and marketing process of the “Tres Hermanos” banana plantation, the owner-manager recognizes that there are shortcomings in the production and marketing process, so the project is feasible. The beneficiaries of this project correspond to the owners of the banana plantation, as well as the workers. To comply with the specific objectives of the research, it is proposed to work mostly with data from the primary source; and extract information through field research, using observation, interview and census techniques. The observation technique allows knowing and detailing in the observation sheet the production process and the commercialization channel of the banana company; subsequently used to develop the process map and describe the marketing channel. The interview technique applied to the manager-owner and census applied to a population of 80 employees, contributes to knowing the internal factors of the company; that complemented with the PEST analysis, allows to determine the strengths, weaknesses, opportunities and threats (SWOT) of the banana company. And to identify the association between production and marketing, an analysis of historical data by linear regression is performed. The results highlight: lack of technical training, little knowledge in fertilization, inexperience, price variations, presence of pests, low quality and insufficient connections. For such problems, an improvement plan is proposed as part of the proposal.